Interaksi Ruhani Antara Orang Yang Sudah Meninggal Dengan Orang-Orang Yang Masih Hidup : Studi Tafsir Tematik Ayat-ayat Ruh dalam Tafsir Al-Mishbâh - Ahmad Anis; Kerwanto Kerwanto; Zakaria Husin Lubis (Hidayah : Cendekia Pendidikan Islam dan Hukum Syariah, 2025)
This study aims to analyze M. Quraish Shihab's views on spiritual interaction between the deceased and the living in Tafsir al-Mishbah. This issue is highly urgent because the debate surrounding the soul and the afterlife has existed since the time of the Prophet Muhammad (peace be upon him) and continues to be a polemic to this day. To answer this question, a qualitative research method with a library research approach was used. Primary data came from Tafsir al-Mishbah, where the Quranic verses about the soul were analyzed thematically. Secondary data were obtained from various classical and contemporary tafsir books, hadith books, and books on interpretation methodology to provide a comprehensive understanding. The results show that, according to M. Quraish Shihab, humans are bidimensional beings. Death is not the end of existence, but rather a transition from the mundane realm to the Barzakh realm, where the soul remains alive. Although human knowledge is very limited regarding the unseen realm, interaction between the souls of the living and the deceased is possible, especially through dreams. In conclusion, M. Quraish Shihab argues that souls in the Barzakh realm remain alive and conscious, and can interact with other souls, although in a different way from communication in the physical world.